PERAN AGAMA DALAM MENANGGULANGI KENAKALAN REMAJA PRESPEKTIF PSIKOLOGI ISLAM - Basila, Faruq; Haryanto, Budi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The impact of juvenile delinquency on personal development is increasingly being highlighted in society. The importance of religion is discussed in this article, especially with regard to Islamic psychology. Islamic moral and ethical teachings are said to provide a strong foundation for adolescents to overcome the urge to engage in harmful behavior. This paper presents an Islamic psychology perspective to understand the diversity of human nature in the context of faith by highlighting the integration of Islamic religious principles with adolescent psychological development. Despite prevention and counseling efforts, peer, media, and environmental influences continue to have a significant impact on adolescent delinquency. Research shows that religion, especially Islam, plays a central role in shaping adolescent morality and responsibility. This article reflects on various solution strategies, including the involvement of authorities and the organization of seminars by psychologists. With an emphasis on the role of religion, particularly in Islamic Psychology, this article highlights that religion can be an effective instrument in addressing juvenile delinquency. This research utilized a literature-based qualitative approach with content analysis to gain a comprehensive picture of the role of religion in addressing juvenile delinquency.